2015
DOI: 10.1111/cge.12572
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype analysis impacts testing strategy in patients with Currarino syndrome

Abstract: Currarino syndrome (OMIM 175450) presents with sacral, anorectal, and intraspinal anomalies and presacral meningocele or teratoma. Autosomal dominant loss-of-function mutations in the MNX1 gene cause nearly all familial and 30% of sporadic cases. Less frequently, a complex phenotype of Currarino syndrome can be caused by microdeletions of 7q containing MNX1. Here, we report one familial and three sporadic cases of Currarino syndrome. To determine the most efficient genetic testing approach for these patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Large deletions or chromosome rearrangement involving 7q36 are related with holoprosencephaly (HPE) and CS due to haploinsufficiency of sonic hedgehog ( SHH ) and MNX1 . Some previous studies reported patients with a deletion or chromosome rearrangement involving 7q36 [ 3 4 14 17 27 28 29 30 31 32 33 34 ]. In these patients, microcephaly was the predominant craniofacial finding of HPE, and hypotelorism, ptosis, and midface hypoplasia were commonly associated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large deletions or chromosome rearrangement involving 7q36 are related with holoprosencephaly (HPE) and CS due to haploinsufficiency of sonic hedgehog ( SHH ) and MNX1 . Some previous studies reported patients with a deletion or chromosome rearrangement involving 7q36 [ 3 4 14 17 27 28 29 30 31 32 33 34 ]. In these patients, microcephaly was the predominant craniofacial finding of HPE, and hypotelorism, ptosis, and midface hypoplasia were commonly associated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patient 16 also exhibited multiple associated anomalies including ptosis, bifid uvula, choanal atresia, laryngomalacia, Sprengel's deformity (congenital elevation of the scapula), cardiac anomalies, and umbilical hernia. According to the diagnostic algorithm proposed by Cuturilo et al [ 4 ], patients with CS exhibiting growth delay and/or developmental delay and/or facial dysmorphic features should be evaluated by a chromosomal microarray. Large deletions and complex rearrangements involving the 7q36 region have been identified in many previous reports [ 3 4 14 17 27 28 29 30 31 32 33 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, distal vertebrae (S4 and S5) are presented as nonsegmented hemivertebrae. In Currarino syndrome, hemiagenesis or partial unilateral agenesis below S2 is typical (Figures and ) . This rare syndrome is a congenital disorder characterized by partial sacral agenesis, anorectal malformation, and a presacral mass.…”
Section: Item 2: Determine the Type Of Sacral Dysgenesismentioning
confidence: 99%
“…In Currarino syndrome, hemiagenesis or partial unilateral agenesis below S2 is typical ( Figures 6 and 7). 20,21 This rare syndrome is a congenital disorder characterized by partial sacral agenesis, anorectal malformation, and a presacral mass. In type 2, sacral agenesis is partial, bilateral, and symmetric ( Figure 6).…”
Section: Item 2: Determine the Type Of Sacral Dysgenesismentioning
confidence: 99%